Optimizing the Public Satisfaction Index (IKM) to Improve Public Service Quality: A Case Study at the Surabaya Immigration Office - Mustofa, Amirul; Wahyu Deby Leksono, Achmad; Widyawati (PT. Anagata Sembagi Education, 2024)
Increasing public demand for quality public services has placed the Immigration Office in Surabaya under scrutiny. As a provider of administrative services, this office must optimize its performance to meet public expectations. However, maintaining reliability, efficiency, and responsiveness remains a challenge. The Public Satisfaction Index (IKM) is used as a key indicator to measure service quality. This study aims to analyze the efforts to optimize IKM in improving service quality at the Surabaya Immigration Office. The research employs a qualitative method with a case study approach, collecting data through interviews with passport applicants and public satisfaction surveys. The aspects measured include reliability, assurance, tangibles, empathy, and responsiveness. The data were analyzed to determine how each aspect affects public satisfaction and to identify areas for improvement to enhance the IKM. The study results indicate that service reliability reached 85%, but internal efficiency still needs improvement. Assurance contributed 78%, with technical issues requiring attention. Tangibles were rated at 82%, though facility modernization is necessary. Empathy received 68%, highlighting the need for improved attention from staff during peak workloads. Responsiveness was rated at 70%, with a need for increased consistency in providing personal attention. Recommendations include regular training and performance evaluations to ensure consistent service standards. The Surabaya Immigration Office should consider increasing staff or utilizing technology, such as online applications, to handle applicant surges and expedite administrative processes. Additional staffing and resource allocation improvements are essential, especially in primary service areas, to maintain responsiveness and empathy.